Anti-biomolecule adhesion colloid particles and preparation method thereof

By adding an appropriate amount of double-ion polymer to the plastic glue particles and kneading at a specific temperature, the problem of plastic glue particles sticking to biological molecules is solved, achieving a simple, environmentally friendly and efficient anti-adhesion effect.

CN113894961BActive Publication Date: 2025-04-01TAIWAN SOKOU INDS KOFUN YUUGENKOUSHI +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111218924.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-20
Publication Date
2025-04-01
Estimated Expiration
2041-10-20

AI Technical Summary

Technical Problem

Existing plastic glue particles are prone to stick to biomolecules during use, resulting in hygiene problems. The existing anti-touch processing methods are cumbersome and unfriendly to the environment.

Method used

By mixing the double-ion polymer with plastic raw materials and kneading at a specific temperature, anti-stick plastic glue particles are prepared. The weight percentage of the double-ion polymer is between 0.1% and 3%, which can significantly reduce the adhesion of biomolecules.

Benefits of technology

It achieves good anti-adhesion effect of plastic rubber particles, simplifies processing steps, reduces environmental pollution, is almost non-toxic to the human body, and is suitable for a wide range of daily necessities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113894961B_ABST
    Figure CN113894961B_ABST
Patent Text Reader

Abstract

Some embodiments of the present disclosure provide an anti-adhesive plastic granule, comprising a plastic raw material and a diionic polymer distributed among the plastic raw material. Some embodiments of the present disclosure also provide a method for manufacturing an anti-adhesive plastic granule, comprising: providing a plastic raw material; providing a diionic polymer; mixing the plastic raw material and the diionic polymer to obtain a mixture; performing a mixing process step on the mixture at a temperature between 150°C and 280°C to obtain plastic granules. The anti-adhesive plastic granules and the manufacturing method of the present disclosure melt the diionic polymer and the plastic raw material together to form an anti-adhesive plastic granule, which not only has an excellent anti-adhesive effect, but also avoids the risk of peeling when the diionic polymer is coated on the plastic surface, reduces the amount of diionic polymer used, simplifies the cumbersome steps of processing the diionic polymer into the plastic raw material, and reduces the use of organic solvents, and has better environmental value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a plastic granule having resistance to biomolecule adhesion and a method for manufacturing the same, and in particular to a plastic granule containing polypropylene granules and a method for manufacturing the same. Background Art

[0002] Plastic pellets are a type of high molecular polymer (molecular weight, for example, at least 10,000 g / mol) that is plastic during the manufacturing process. Due to the different monomers in the high molecular polymer (such as polyethylene, polypropylene, polyvinyl chloride, etc.), plastic pellets with different properties can be formed. Since plastic pellets have excellent plasticity, easy processing and easy storage, the finished products made of plastic pellets are widely used in life.

[0003] For example, polypropylene (PP) granules are formed by the polymerization reaction of propylene. The finished plastic products made of polypropylene granules have good mechanical properties, high heat deformation temperature, and are not easily corroded by inorganic salts and acids or alkalis. They are often used in products such as car batteries, toys, cassette casings, pudding boxes, etc.

[0004] However, the finished products made of existing plastic pellets inevitably have the problem of easy adhesion of biological molecules (molecules carried by organisms, such as molecules carried by viruses, bacteria, molds, etc.), which may lead to health problems such as pollution breeding over time, causing concerns about long-term use. In addition, the existing processing methods of anti-adhesive plastic pellets (such as coating the surface with an anti-adhesive layer) often require multiple additional processing steps in addition to the melting step of the plastic pellets, and an organic solution must be used in the reaction process. Not only are the steps cumbersome, but the discharge of waste liquid is not friendly to the environment.

[0005] In summary, how to provide a plastic pellet that is easy to manufacture, environmentally friendly, and has a good anti-sticking effect is a problem to be solved. Summary of the invention

[0006] Therefore, one aspect of the present disclosure is to provide an anti-adhesive plastic pellet comprising a plastic raw material and a diionic polymer distributed between the plastic raw materials.

[0007] In some embodiments, the plastic raw material comprises a homopolymer, a copolymer, or a combination thereof, wherein the constituent monomers of the homopolymer or the copolymer comprise vinyl chloride, propylene, styrene, ethylene, urethane, methyl methacrylate, phenylene sulfide, formaldehyde, phenylene ether, urea, butylene terephthalate, ethylene terephthalate, or amide.

[0008] In some embodiments, the diionic polymer comprises AU n BU mA block copolymer, a random copolymer or an alternating copolymer, wherein AU represents -CR 1 R 2 -Structure shown, BU represents -CH2CR 2 R 3 -or-CR 2 R 4 CH2CR 2 R 5 - shown in the structure, m represents an integer from 5 to 120, n represents an integer from 5 to 120, wherein R 1 represents a linear, branched or cyclic alkyl group having 3 to 18 carbon atoms, an ester group, an aromatic group or a heteroaryl group having 5 to 12 carbon atoms, R 2 represents a hydrogen atom or a methyl group, R 3 Indicates -COOR' or -CONR'H, R 4 represents a hydrogen atom or a carboxyl group, and when R 4 When it is a hydrogen atom, R 5 is -COOR' or -CONR"H, where R 4 When it is carboxyl, R 5 is a cationic group, wherein R' and R" represent a betaine group, a sulfobetaine group or a carboxybetaine group respectively.

[0009] In some embodiments, if the weight percentage of the plastic particles is 100%, the weight percentage of the diionic polymer is between 0.1% and 3%.

[0010] In some embodiments, the plastic pellets further include additives distributed among the plastic raw materials.

[0011] In some embodiments, the auxiliary agent comprises a plasticizer, a stabilizer, a lubricant or a combination thereof.

[0012] Another aspect of the present disclosure is to provide a method for manufacturing anti-sticking plastic pellets, comprising: providing a plastic raw material; providing a diionic polymer; mixing the plastic raw material and the diionic polymer to obtain a mixture; performing a mixing process step on the mixture at a temperature between 150°C and 280°C to obtain plastic pellets.

[0013] In some embodiments, the step of mixing the plastic raw material and the diionic polymer includes: if the total weight percentage of the plastic raw material and the diionic polymer is 100%, the weight percentage of the diionic polymer added is between 0.1% and 3%.

[0014] In some embodiments, the step of mixing the plastic raw material and the dual-ion polymer comprises: heating the plastic raw material and the dual-ion polymer at a temperature below 150°C.

[0015] In some embodiments, after the step of providing plastic raw materials, it also includes: providing an auxiliary agent; mixing the auxiliary agent with the plastic raw materials to obtain a preprocessed product; mixing the preprocessed product and a diionic polymer to obtain a processing mixture; performing a mixing process step on the processing mixture at a temperature between 150°C and 280°C to obtain plastic granules. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] To make the above and other objects, features, advantages and embodiments of the present disclosure more clearly understood, the detailed description of the accompanying drawings is as follows:

[0017] Figure 1 A flow chart of a method for manufacturing plastic pellets according to some embodiments of the present disclosure is shown.

[0018] Figure 2 FIG. 4 is a graph showing a comparison of relative attachment ratios of E. coli in an E. coli attachment test according to an embodiment of the present disclosure.

[0019] Figure 3 FIG. 4 is a graph showing a comparison of relative fibrinogen attachment ratios in a fibrinogen attachment test according to an embodiment of the present disclosure.

[0020] Figure 4 FIG. 4 is a graph showing a comparison of relative cell attachment ratios in a cell attachment assay according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0021] It is understood that the different implementations or examples provided below may implement different features of the objectives of the present disclosure. The examples of specific components and arrangements are used to simplify the present disclosure rather than to limit the present disclosure. Of course, these are only examples and are not intended to be limiting. For example, the description of the first feature formed on the second feature described below includes direct contact between the two, or other additional features are separated from the two without direct contact. In addition, the present disclosure may repeat reference numbers and / or symbols in multiple embodiments. Such repetition is for simplicity and clarity, and does not represent the relationship between the various embodiments and / or configurations discussed.

[0022] The terms used in this specification generally have common meanings in the art and in the context in which they are used. The embodiments used in this specification, including examples of any term discussed herein, are merely illustrative and do not limit the scope and meaning of the disclosure or any exemplary term. Likewise, the disclosure is not limited to some of the embodiments provided in this specification.

[0023] In addition, spatially relative terms, such as "lower", "upper", etc., are used to facilitate describing the relative relationship of an element or feature to other elements or features in the drawings. These spatially relative terms are intended to encompass different orientations of the device when in use or operation in addition to the orientation shown in the drawings. The device may be otherwise oriented (e.g., rotated 90 degrees or in other orientations), and the spatially relative descriptions used herein may be interpreted accordingly.

[0024] In this document, unless the context specifically limits the article, "a", "an" and "the" may refer to a single or multiple items. It will be further understood that "comprising", "including", "having" and similar words used in this document specify the features, regions, integers, steps, operations, elements and / or components described therein, but do not exclude other features, regions, integers, steps, operations, elements, components, and / or groups thereof.

[0025] All references cited herein are treated as if each individual reference or patent application was specifically and individually incorporated by reference. If a definition or use of a term in a cited document is inconsistent or contrary to the definition of that term herein, the definition of that term herein shall apply.

[0026] Several embodiments are listed below to further illustrate the touch device of the present invention. However, they are only for illustration and are not intended to limit the present invention. The protection scope of the present invention shall be subject to that defined in the claims.

[0027] As mentioned above, the present disclosure provides an anti-adhesive plastic granule and a method for manufacturing the same. By mixing a diionic polymer with a plastic raw material (such as polypropylene), the diionic polymer is distributed between the plastic raw materials, so that only a small amount of the diionic polymer is needed to achieve the anti-adhesive effect of the plastic granule. The diionic polymer is almost non-toxic to the human body and can be widely used in daily necessities.

[0028] See also Figure 1 , Figure 1 A flow chart of a method 100 for manufacturing plastic pellets according to some embodiments of the present disclosure is shown. First, as shown in step S110, a plastic raw material is provided.

[0029] In some embodiments, the plastic raw material comprises a homopolymer, a copolymer, or a combination thereof, wherein the constituent monomers of the homopolymer or the copolymer comprise vinyl chloride, propylene, styrene, ethylene, urethane, methyl methacrylate, phenylene sulfide, formaldehyde, phenylene ether, urea, butylene terephthalate, ethylene terephthalate, or amide.

[0030] In some embodiments, the plastic raw material is polypropylene, which is formed by polymerization and drying of propylene monomers. Depending on the position of the branched atoms, the polypropylene can have different stereostructures. In some embodiments, the polypropylene can be a polypropylene that is gelled after heating and granulation.

[0031] In some embodiments, after the step of providing the plastic raw material, the process further comprises: providing an auxiliary agent; mixing the auxiliary agent with the plastic raw material to obtain a pre-processed product, and then using the pre-processed product to perform subsequent processes. In some embodiments, the auxiliary agent comprises a plasticizer, a stabilizer (e.g., an organic tin stabilizer, a barium zinc stabilizer, or a combination thereof), a lubricant (e.g., an internal lubricant (e.g., stearic acid alcohol, stearamide, butyl stearate, monoglyceride stearate, or a combination thereof) or an external lubricant (e.g., paraffin, stearic acid, polyethylene wax, oxidized polyethylene wax, or a combination thereof)) and other additional additives that help improve the properties of the plastic raw material. That is, according to the process and the finished product requirements, before mixing the plastic raw material and the diionic polymer, the plastic raw material can be pre-processed by mixing the plastic raw material and the additives under suitable reaction conditions to obtain a pre-processed product, and the pre-processed product can be directly used in the subsequent steps, and the same or similar steps as the subsequent manufacture of plastic pellets can be followed (for example, mixing the pre-processed product and the diionic polymer to obtain a processed mixture; then, performing a mixing process on the processed mixture at a temperature between 150°C and 280°C to obtain plastic pellets), thereby obtaining plastic pellets with improved properties compared to using plastic raw materials.

[0032] Next, as shown in step S120 , a dual ion polymer is provided.

[0033] In some embodiments, the diionic polymer is in any form, such as powder. In one embodiment, the diionic polymer comprises a structure as described in Taiwan Patent Publication No. TW I496819 B, that is, the diionic polymer may, for example, comprise the following formula (1) or formula (2) described AU n BU m block copolymers, random copolymers or alternating copolymers.

[0034]

[0035]

[0036] AU represents the formula (1) in which -CR 1 R 2 - is a divalent methylene structure having a substituent, BU represents -CH2CR in formula (1) 2 R 3 - a divalent ethylene structure having a substituent, or -CR in formula (2) 2 R 4 CH2CR2 R 5 - is a divalent propyl group structure having a substituent, m represents an integer of 5 to 120, and n represents an integer of 5 to 120, wherein AU has an anchoring group, and BU has a zwitterionic group or a pseudo-zwitterionic group.

[0037] Specifically, the above R 1 represents a linear, branched or cyclic alkyl group or an ester group (i.e. -COOR x , where R x represents a linear, branched or cyclic alkyl group having 3 to 18 carbon atoms, an aromatic group or a heteroaryl group having 5 to 12 carbon atoms. 2 represents a hydrogen atom or a methyl group. 3 represents a structure of -COOR' or -CONR"H, wherein R' and R" independently represent a betaine group, a sulfobetaine group or a carboxybetaine group. 4 represents a hydrogen atom or a carboxyl group (-COOH), where R 4 When it is a hydrogen atom, R 5 is -COOR' or -CONR"H, and when the above R 4 When it is carboxyl, R 5 For example, it may be a cationic group (for example, it may be N,N-dimethylammnio-ethylene-1-amino-vinyl, N,N-dimethylammnio-propylene-1-amino-vinyl, N,N-dimethylammnio-butylene-1-amino-vinyl and N,N-dimethylammnio-pentylene-1-amino-vinyl).

[0038] Next, as shown in step S130, the plastic raw material and the diionic polymer are mixed to obtain a mixture.

[0039] In some embodiments, in the step of mixing the plastic raw material and the diionic polymer, if the weight percentage of the total reactants (e.g., the total of the plastic raw material and the diionic polymer; if an additive is added, the total of the plastic raw material, the diionic polymer and the additive) is 100%, the weight percentage (wt) of the diionic polymer added is between 0.1% and 3% (e.g., 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or any value in the aforementioned range). In some embodiments, when the weight percentage of the diionic polymer added is at least 0.1%, the adhesion of biological molecules (e.g., proteins) can be significantly reduced compared to when no diionic polymer is added, thereby reducing biological adhesion (e.g., cells or bacteria). Specifically, the relative attachment ratios of bacteria, proteins, and cells without adding the diionic polymer are calculated as 100%, respectively. Then, when the diionic polymer is added at a weight percentage of 0.5%, more than 96% of bacteria attachment (relative attachment ratio less than 4%), more than 66% of proteins attachment (relative attachment ratio less than 34%), and more than 91% of human cells attachment (relative attachment ratio less than 9%) can be avoided compared to when the diionic polymer is not added. It should be noted that if the weight percentage of the diionic polymer is lower than the lower limit, the anti-adhesion effect of the plastic particles of the final product is not good (the "anti-adhesion" of the plastic particles referred to in the present disclosure refers to the property of preventing non-specific adhesion of biological molecules. If the relative attachment ratio of the group without adding the diionic polymer is regarded as 100%, the relative attachment ratio of the plastic particles is not greater than 40%). If the weight percentage is higher than the upper limit, not only the cost is increased, but also the increase in the anti-adhesion effect is limited.

[0040] In some embodiments, a diionic polymer with a suitable melting point can be selected and matched with the mixing temperature, for example, the melting point can be 150° C. to 280° C., so that during subsequent mixing, the diionic polymer can be evenly dispersed in the plastic raw material, thereby improving the dispersion uniformity of the diionic polymer in the final product.

[0041] In some embodiments, preliminary heating can be performed in the step of mixing the plastic raw material and the diionic polymer to improve the mixing efficiency. For example, the plastic raw material and the diionic polymer are heated at a temperature below 150° C. to improve the mixing efficiency of the plastic raw material and the diionic polymer, so that the diionic polymer is evenly distributed among the diionic polymers. However, the mixing method of the present disclosure is not limited to this, and other methods that help improve the mixing efficiency of the plastic raw material and the diionic polymer (such as stirring conditions) are also included in the scope of the present disclosure.

[0042] In some embodiments, in the step of mixing the plastic raw materials and the diionic polymer, suitable additives (such as the aforementioned plasticizers, stabilizers, lubricants, etc.) can also be added according to process requirements to help improve the mixing efficiency, accelerate the speed of subsequent process reactions, or help adjust the physical and chemical properties of the final product plastic pellets.

[0043] Next, as shown in step S140, a mixing step is performed on the mixture at a temperature between 150°C and 280°C (for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C or any value in the aforementioned range) to obtain plastic pellets.

[0044] In some embodiments, the step of performing a kneading process on the mixture at a temperature between 150° C. and 280° C. includes uniformly melting the mixture at 190° C. Then, the mixture is plasticized and cooled by a twin-screw extruder to produce plastic pellets.

[0045] In some embodiments, the shape and size of the plastic pellets are not limited. For example, the plastic pellets can be formed into a strip-shaped test piece with a length of 120 mm, a width of 70 mm, and a thickness of 0.5 mm.

[0046] In some embodiments, the melting points of the additives (if added), plastic raw materials, and the dual-ion polymer can be considered, and the appropriate mixing temperature can be adjusted accordingly to avoid uneven mixing due to the large difference in the melting points of the three. The number of mixing processes (such as a single mixing process or more than two stage mixing processes, etc.) can also be adjusted according to the aforementioned factors to improve the uniformity of mixing. For example, the mixing temperature must not be lower than 150°C to avoid incomplete plasticization of the plastic, resulting in uneven mixing of the dual-ion polymer, poor dispersion, and even causing the plastic pellets of the final product to have visible white spots, reduce their transparency, affect visual perception, and limit the application field of downstream products made from the plastic pellets. In addition, if the dual-ion polymer has poor dispersibility, the obtained plastic pellets may not be able to effectively resist adhesion.

[0047] In some embodiments, the mixing process step has an unlimited time, for example, it can be 20 minutes to 30 minutes or longer, so that the additive (if added), the plastic raw material, and the dual-ion polymer are evenly mixed.

[0048] Several embodiments are used below to illustrate the application of the present disclosure, but they are not intended to limit the present disclosure. Those skilled in the art of the present disclosure can make various changes and modifications without departing from the spirit and scope of the present disclosure.

[0049] Example 1: Preparation of polypropylene pellets

[0050] First, polypropylene is used as a plastic raw material. Polypropylene and diionic materials of different weight percentages are pre-mixed in a mixer (Qiaolong Machinery Co., Ltd.) at a speed of not less than 50 rpm (Revolution(s) PerMinute) to form a mixture (if the weight percentage of the total diionic polymer and polypropylene is regarded as 100%, the weight percentage of the diionic polymer is 0.5%, 1%, and 2% respectively). Then, the mixture is put into a twin-screw extruder (Leistritz Company, model ZSE27MAXX) for melt mixing processing, the screw speed is 230 rpm, the working temperature is 190°C, and polypropylene pellets are produced. Finally, the polypropylene pellets are placed in a hot press molding machine to obtain a polypropylene test piece. The above diionic polymer is generally manufactured according to the method disclosed in the above Taiwan Patent Announcement No. TW I496819B (provided by Prebo Biotech Co., Ltd.). In order to compare whether the polypropylene test piece with added diionic polymer can resist biomolecule adhesion and the degree of anti-adhesion, the polypropylene test piece obtained in this example is used to carry out the subsequent examples.

[0051] Example 2: Anti-bacterial adhesion effect of polypropylene test piece

[0052] In this example, an Escherichia coli adhesion test was used to evaluate the anti-adhesion effect of the polypropylene test piece on bacteria.

[0053] First, E. coli was cultured with LB (Lysogeny Broth) culture medium to obtain a bacterial solution with an OD value of 1 at a wavelength of 660 nanometers. Then, the polypropylene test piece was covered with 1 ml of the bacterial solution and cultured in an incubator at 37°C and 150 rpm for 24 hours. Then, the unattached E. coli on the polypropylene test piece was washed away with phosphate buffered saline (PBS) buffer, and the polypropylene test piece was immersed in glutaraldehyde for 24 hours to fix the E. coli on the polypropylene test piece. Then, the E. coli attached to the polypropylene test piece was observed with a laser scanning conjugate electron microscope, and the amount of E. coli attached per unit area in each group was calculated. Next, the attachment amount of the polypropylene test piece without the addition of the diionic polymer was converted to 100% (i.e., the relative attachment ratio), and the polypropylene test piece without the addition of the diionic polymer was used as the comparison benchmark for the relative attachment ratio. At the same time, the attachment amount of the polypropylene test piece group with the addition of the diionic polymer was converted to the relative attachment ratio, and the comparison results are shown in FIG. Figure 2 .

[0054] Figure 2In the figure, the horizontal axis represents different added contents of the diionic polymer, and the vertical axis represents the relative attachment ratio of Escherichia coli per unit area.

[0055] Figure 2 For example, when the weight percentage of the diionic polymer is 0.5%, the relative attachment ratio is 3.41%; when the weight percentage of the diionic polymer is 1%, the relative attachment ratio is 1.32%; when the weight percentage of the diionic polymer is 2%, the relative attachment ratio is 0.73%. That is, when the weight percentage of the diionic polymer is 0.5%, the bacterial attachment amount can be reduced by more than 96% compared with the group without the diionic polymer, and as the weight percentage gradually increases to 2%, the bacterial attachment amount can be reduced by more than 99%. As the amount of diionic polymer added increases, the anti-bacterial adhesion effect increases accordingly.

[0056] Example 3: Anti-protein adhesion effect of polypropylene test piece

[0057] In this example, fibrinogen was used as the test protein, and the enzyme-linked immunosorbent assay (ELISA) was used to evaluate the anti-adhesion effect of the polypropylene test piece on the protein.

[0058] First, the polypropylene test piece was soaked in PBS buffer for 30 minutes, and the liquid on the polypropylene test piece was dried. Then, a fibrinogen solution with a concentration of 1 mg / ml was added to the polypropylene test piece, and the polypropylene test piece was placed in an oven at 37°C for 30 minutes for drying to allow the fibrinogen to adhere to the polypropylene test piece. Then, the polypropylene test piece was washed with PBS buffer for 3 times, and the liquid on the polypropylene test piece was removed to remove the unbound fibrinogen and impurities in the fibrinogen solution.

[0059] Next, a blocking step was performed to fill the portion of the polypropylene test piece that was not adsorbed with fibrinogen. The blocking step was performed by applying 1 ml of a 1 mg / ml bovine serum albumin (BSA) solution to the polypropylene test piece, placing the solution in an oven at 37° C. for 30 minutes, then washing the polypropylene test piece three times with a PBS buffer solution, and then removing the liquid from the polypropylene test piece.

[0060] Next, a first antibody capable of binding to fibrinogen was applied to the polypropylene test piece, and then dried, and the polypropylene test piece was washed with PBS buffer for 3 times, and then the liquid on the polypropylene test piece was removed. Then, the above-mentioned blocking step was performed again.

[0061] Then, 1 ml of a second antibody with a concentration of 1 mg / ml (the second antibody is specific to the first antibody and is labeled with a group for subsequent color development (e.g., horseradish peroxidase (HRP))) is applied to the polypropylene test piece, and after drying, the polypropylene test piece is washed 5 times with PBS buffer, and the liquid on the polypropylene test piece is removed.

[0062] Next, the polypropylene test piece was transferred to a 24-well plate, and 0.5 ml of the color developer 3,3',5,5'-tetramethylbenzidine (TMB) was applied to the polypropylene test piece, and the reaction was allowed to proceed for 6 minutes until the color was developed. Then, 0.5 ml of 1M sulfuric acid was applied to the polypropylene test piece to terminate the color development reaction. Finally, 200 μL of the reaction solution was pipetted into a 96-well plate, and the absorbance of the sample solution at a wavelength of 450 nm was measured using a microplate absorbance reader to infer the amount of fibrinogen attached to the polypropylene test piece. Next, the amount of attached polypropylene test piece without the addition of the diionic polymer was converted to a relative attachment ratio of 100% as the conversion basis for the relative attachment ratio. The amount of attached polypropylene test piece group with the addition of the diionic polymer was then converted to a relative attachment ratio, and the comparison results of the relative attachment ratios of each group are shown in FIG. Figure 3 .

[0063] Figure 3 In the figure, the horizontal axis represents different added contents of the dual ionic polymer, and the vertical axis represents the relative attachment ratio of fibrinogen per unit area.

[0064] Figure 3 For example, when the weight percentage of the diionic polymer is 0.5%, the relative attachment ratio is 34%; when the weight percentage of the diionic polymer is 1%, the relative attachment ratio is 30%; when the weight percentage of the diionic polymer is 2%, the relative attachment ratio is 32%. That is, when the weight percentage of the diionic polymer is 0.5%, the amount of protein attachment can be reduced by at least 65% compared to the group without adding the diionic polymer.

[0065] Example 4: Anti-cell adhesion effect of polypropylene test piece

[0066] In this example, human fibrosarcoma cells (HT-1080 cell line, a cell line easily available to those skilled in the art) were used to perform a cell adhesion test to evaluate the anti-adhesion effect of the polypropylene test piece on cells.

[0067] First, HT-1080 cells were placed in a cell culture dish and cultured in DMEM (Dulbecco's modified Minimal Essential Medium) containing 10% fetal bovine serum. The cells were cultured in a cell culture incubator at 37°C and 5% CO2 for 7 days, and then the culture medium was removed. The cells were then washed three times with PBS buffer. Trypsin was then added, and the cells were left to detach from the culture dish after being tapped for six minutes. DMEM containing 10% fetal bovine serum was added and mixed evenly. The cells were centrifuged to remove excess trypsin and precipitate the cells. The cells were then suspended to a cell density of 1.0 x 10 4 cells / mL of cell suspension.

[0068] Take 1 ml of the cell suspension and cover the surface of the polypropylene test piece. After culturing in a cell culture incubator for 24 hours, rinse the non-attached cells on the surface of the polypropylene test piece with PBS buffer and use an inverted microscope to photograph the cell adhesion on the plastic sheet surface. Calculate the cell adhesion amount per unit area in each group. Then, using a method similar to that of Example 2 above, convert the adhesion amount of the polypropylene test piece without the addition of the diionic polymer into a 100% relative adhesion ratio, and convert the adhesion amount of the polypropylene test piece group with the addition of the diionic polymer into a relative adhesion ratio accordingly. The comparison results of the relative adhesion ratios of each group are shown in the figure. Figure 4 .

[0069] Figure 4 For example, when the weight percentage of the diionic polymer is 0.5%, the relative attachment ratio is 8.57%; when the weight percentage of the diionic polymer is 1%, the relative attachment ratio is 15.73%; when the weight percentage of the diionic polymer is 2%, the relative attachment ratio is 1.40%. That is, when the weight percentage of the diionic polymer is 0.5%, the cell attachment amount can be reduced by more than 91% compared with the group without the addition of the diionic polymer. When the weight percentage of the diionic polymer is 2%, the cell attachment amount can be reduced by more than 98% compared with the group without the addition of the diionic polymer.

[0070] Example 5: Cytotoxicity of Polypropylene Test Pieces

[0071] In this example, mouse fibroblasts (L929 cell line, a cell line easily available to those skilled in the art) were used to perform an in vitro cytotoxicity test to evaluate whether the polypropylene test piece was cytotoxic.

[0072] First, the L929 cell line was cultured in a culture dish, wherein the culture medium was minimal essential medium (MEM; hereinafter referred to as MEM culture medium) containing 10% horse serum, and the L929 cell line was cultured at 37°C and 5% CO2 for 7 days. Then, the MEM culture medium was removed, and the cells were washed 3 times with PBS buffer. Next, trypsin was added to the culture dish, and after standing for 6 minutes, the culture dish was tapped to detach the L929 cell line from the culture dish, and MEM culture medium was added to the culture dish to suspend the L929 cell line in the MEM culture medium. Next, the MEM culture medium was transferred to a centrifuge tube for centrifugation to collect the cell precipitate. Next, the cell precipitate was suspended in MEM culture medium to obtain cell fluid, and the cell fluid was adjusted to contain 1.0×10 per milliliter of cell fluid with an appropriate amount of MEM culture fluid. 5 cells or 1.5×10 5 L929 cell line (1.0×10 5 cells / mL or 1.5×10 5 cells / mL).

[0073] Next, extract the substances in the polypropylene test piece. Specifically, MEM culture medium was used to cover the polypropylene test piece, wherein the extraction was carried out at 37°C and 150rpm for 24 hours to obtain each group of extracts (experimental group, positive control group, negative control group). Specifically, the ratio of the polypropylene test piece area: MEM culture medium volume was 6 square centimeters: 1 milliliter, and zinc diethyl-dithiocarbamate (ZDEC) and high-density polyethylene (HDPE) were extracted with MEM culture medium respectively, and the two were used as the positive control group and the negative control group respectively, wherein the ratio of ZDEC mass: MEM culture medium volume was 0.1 grams: 1 milliliter, and the ratio of HDPE mass: MEM culture medium volume was 0.2 grams: 1 milliliter.

[0074] Next, add 0.1 ml of 1.0×10 5Cells / ml of cell solution were added to a 96-well culture plate and cultured at 37°C, 5% CO2 for 24 hours. Then, the culture medium in the culture plate was removed, and 0.1 ml of the experimental group extract, MEM culture medium, positive control group extract, and negative control group extract were added to the 96-well culture plate, respectively, and cultured at 37°C, 5% CO2 for another 24 hours. Then, 0.1 ml of 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenylamino)carbonyl]-2H-tetrazolium hydroxide (hereinafter referred to as XTT reagent) was added to the 96-well culture plate and cultured at 37°C, 5% CO2 for 3 hours. Subsequently, the 96-well culture plate was taken out and the OD value at a wavelength of 450 nm was measured using a microplate spectrophotometer to obtain the absorbance values ​​of the experimental group, the blank group, the positive control group and the negative control group, respectively. The cell survival rate was then calculated using the following formula (Formula (3)).

[0075]

[0076] To facilitate observation of cell appearance changes, 1.5×10 5 cells / ml of cell solution was added to a 12-well plate. After 24 hours of culture, the culture medium was removed and 1 ml of the experimental group extract, MEM culture medium, positive control group extract and negative control group extract were added to the 12-well culture plate. The plates were also cultured for 24 hours and observed.

[0077] The cell appearance changes, cell density changes and cytotoxicity levels of each group were evaluated according to the standards of the cell change degree evaluation table in Table 1 below, and the evaluation results of each group were integrated in Table 2 below.

[0078] Table 1. Evaluation table of cell change degree

[0079]

[0080]

[0081] Table 2. Comparison of cell changes in each group

[0082]

[0083] The results in Table 2 show that the cytotoxicity of the polypropylene test piece with a weight percentage of 0.5% diionic polymer is 0; and if the weight percentage of the diionic polymer in the polypropylene test piece is increased to 1% and 2%, the cytotoxicity is only slightly increased to 1, which is almost non-cytotoxic and almost harmless to the human body. Therefore, the polypropylene test piece with a diionic polymer in the range of 0.5% to 2% is almost harmless to the human body and can be widely used in various daily necessities.

[0084] As can be seen from the above embodiments, the anti-adhesive plastic pellets and manufacturing methods disclosed herein, which melt the diionic polymer and plastic raw materials together to form anti-adhesive plastic pellets, not only have excellent anti-adhesive effects, but also the diionic polymer is dispersed in the plastic pellets, which can avoid the risk of peeling of the diionic polymer layer when the diionic polymer is coated on the plastic surface, can prolong the anti-adhesive effect of the plastic pellets, and can reduce the amount of diionic polymer used compared to the direct coating method. In addition, it can also simplify other cumbersome steps when processing the diionic polymer into the plastic raw materials (such as surface grafting, surface separation, bionic adhesion or surface coating methods), and reduce the use of organic solvents, which is more environmentally friendly and has better environmental value.

[0085] Although the present disclosure has been disclosed as above with several specific embodiments, various modifications, changes and substitutions may be made to the above disclosure, and it should be understood that in some cases, certain features of the embodiments of the present disclosure will be adopted but other features will not be used without departing from the spirit and scope of the present disclosure. Therefore, the spirit of the present disclosure and the scope of the claims should not be limited to the above exemplary embodiments.

[0086]

Explanation of symbols

[0087] 100: Method

[0088] S110, S120, S130, S140: steps.

Claims

1. A method for producing anti-sticking plastic granules, characterized in that: Include: Providing a plastic raw material, wherein the plastic raw material is polypropylene; Provided is a diionic polymer, the diionic polymer comprising AU n BU m A block copolymer, a random copolymer or an alternating copolymer, AU stands for -CR 1 R 2 -Structure shown, BU represents -CH2CR 2 R 3 -or-CR 2 R 4 CH2CR 2 R 5 -, m represents an integer from 5 to 120, n represents an integer from 5 to 120, Where R 1 represents a linear, branched or cyclic alkyl group having 3 to 18 carbon atoms, an ester group, an aromatic group or a heteroaryl group having 5 to 12 carbon atoms, R 2 represents a hydrogen atom or a methyl group, R 3 Indicates -COOR' or -CONR'H, R 4 represents a hydrogen atom or a carboxyl group, When R 4 When it is a hydrogen atom, R 5 is -COOR' or -CONR"H, R' and R" independently represent betaine, sulfobetaine or carboxybetaine, when R 4 When it is carboxyl, R 5 It is a cationic group; Mixing the plastic raw material and the diionic polymer to obtain a mixture, wherein if the total weight percentage of the plastic raw material and the diionic polymer is 100%, the weight percentage of the diionic polymer added is between 0.1% and 3%; The mixture is subjected to a mixing process step at a temperature between 150° C. and 280° C. to obtain the plastic pellets.

2. The method according to claim 1, wherein the step of mixing the plastic raw material and the dual-ion polymer comprises: heating the plastic raw material and the dual-ion polymer at a temperature below 150°C.

3. The method according to claim 1, further comprising, after the step of providing the plastic raw material: Provide auxiliary agents; mixing the auxiliary agent with the plastic raw material to obtain a pre-processed product; Mixing the pre-processed material and the dual ion polymer to obtain a processed mixture; The mixing step is performed on the processing mixture at a temperature between 150° C. and 280° C. to obtain plastic pellets.

4. The method according to claim 3, wherein the auxiliary agent comprises a plasticizer, a stabilizer, a lubricant or a combination thereof.

5. An anti-sticking plastic pellet, characterized in that: Produced by the method of claim 1.

Citation Information

Patent Citations

  • Built-in antimicrobial plastic resins and methods for making the same

    CN106715568A

  • Biomimetic agent for Anti-biofouling coating and method for making the same

    TW201520246A